Children's rights in the United States in search of a national policy - Walker, Nancy E.; Brooks, Catherine M.; Wrightsman, Lawrence S.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1999)
The Rights of Children in the United States provides discussion on: the historical and contextual perspective on the rights of children; the UN Convention on the Rights of the Child; and the differing views on children's rights and competencies.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Children's rights -- United States; Children -- Legal status, laws, etc. -- United States; Electronic books